Perspektywa interpretatywna w naukach o zarządzaniu - Sułkowski, Łukasz (Interpretative Perspectives in Management Science, 2006)
For the last few decades there has been a development of ideas in management sciences that can be located the symbolic-interpretative tendency. Many different management methods and techniques using the assumptions of this approach have been distinguished. It seems, however, that these methods are little known and little popularised in management in Poland. Scarce is the knowledge of the issue of development of the interpretative tendency and methods this tendency uses. In reality, however, certain methods are applied in management without the consciousness of their interpretative sources. Field methods and participating observations as well as deepened case studies are meant here. From the Polish point of view it is worthwhile to conduct research on the application of other interpretative methods in management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 135-143